"When I got the news": Aboriginal fathers in the Kimberley region yarning about their experience of the antenatal period. (14th July 2020) - Carlin, Emma; Cox, Zaccariah; Spry, Erica; Monahan, Conor; Marley, Julia V.; Atkinson, David
Abstract: Issue addressed: Paternal involvement during the antenatal period is recognised as a positive contributor to a child's health and developmental outcomes. Little is known about Aboriginal Australian men's experiences and perceptions during their partner's antenatal period. Methods: A qualitative yarning methodology was used to explore the experiences of ten Aboriginal Australian fathers during their partner's antenatal period, in a remote Northern Australian town. Results: The study found the participants valued supporting their partners through pregnancy, making positive changes to their lifestyles, and having access to information on pregnancy. Participants described experiencing multiple stressors during the antenatal period that impacted on their social and emotional wellbeing. This is despite the range of protective factors identified by them. Participants had diverse experiences with health care providers during the antenatal period. Conclusions: This study demonstrated that these Aboriginal men valued engagement with antenatal care (ANC) services and highlighted strategies to improve Aboriginal paternal involvement with ANC services. So what?: Enhancing ANC to be inclusive of fathers, through a local co‐design process, could strengthen and support Aboriginal families to achieve improved health and wellbeing outcomes across the family system.